An HSGPS, inertial and map-matching integrated portable vehicular navigation system for uninterrupted real-time vehicular navigation. (11th August 2005) - Basnayake, C.; Mezentsev, O.; Lachapelle, G.; Cannon, M.E.
Robust real-time vehicle positioning is a critical requirement for many in-vehicle technologies. However, no standalone positioning system is capable of providing uninterrupted and accurate vehicular navigation data in all environments that a vehicle could encounter. This paper presents a portable vehicular navigation system that combines high-sensitivity GPS, inertial sensors and map-matching techniques to provide uninterrupted vehicular navigation information in even the harshest environments for individual sensor technologies. This system eliminates the need for complex initialisation routines required for high-end inertial sensors, making it a truly portable system. The map-matching component establishes a link between the vehicle and spatial information useful for many more in-vehicle technologies such as route guidance and location-based services. The system performance is evaluated and presented in an urban centre with extreme levels of GPS signal degradation.